Juridical Review Of The Euthanasia Crime In The Indonesian Criminal Law System - Andhes Hary Zugesthy (UMPurwokerto Law Review, 2020)
AbstractEuthanasia is the act of ending the life of someone who is seriously ill and has a minimal life expectancy intended to relieve suffering. This study aims to identify and analyze the regulation of euthanasia in the Indonesian criminal law system and determine whether euthanasia can be decriminalized under the current Indonesian criminal law system. Patients who are seriously ill and have a minimal life expectancy are often the reason for euthanasia, both on their own and on the wishes of their families. This action is included in Article 344 of the Criminal Code in the Criminal Code. For now, the Indonesian criminal law system is experiencing difficulties in proving euthanasia because there is no detailed criminal formulation applied regarding euthanasia, then decriminalization of euthanasia cannot be justified.Keywords: Legal system, Euthanasia, Decriminalization.AbstrakEthuanasia merupakan tindakan mengakhiri kehidupan seseorang yang sakit parah dan memiliki harapan hidup yang sangat kecil dimaksudkan untuk menghilangkan penderitaan. Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisi pengaturan euthanasia dalam sistem hukum pidana Indonesi serta mengetahui apakah euthanasia dapat didekriminalilasi berdasarkan sistem hukum pidana Indonesia saat ini. Pasien yang menderita sakit parah dan memiliki harapan hidup yang sangat kecil seringkali menjadi alasan untuk dilakukan tindakan euthanasia baik hal tersebut atas keinginan dirinya sendiri maupun atas keinginan keluarganya. Dalam KUHP tindakan ini  masuk ke dalam Pasal 344 KUHP. Untuk saat ini, sistem hukum pidana Indonesia mengalami kesulitan pembuktian euthanasia dikarenakan tidak adanya rumusan pidan secara terperinci diterapkan mengenai euthanasia, kemudian untuk dekriminilasi terhadap euthanasia pun tidak dapat dibenarkan untuk saat ini.Kata Kunci : Sistem hukum, Euthanasia, Dekriminalisasi